Specific Changes in Arabidopsis thaliana Rosette Lipids during Freezing Can Be Associated with Freezing Tolerance - Sy Vu, Hieu; Shiva, Sunitha; Samarakoon, Thilani; Li, Maoyin; Sarowar, Sujon; Roth, Mary R.; Tamura, Pamela; Honey, Samuel; Lowe, Kaleb; Porras, Hollie; Prakash, Neema; Roach, Charles A.; et al. (My University, 2022)
While the roles of a few specific lipids in plant freezing tolerance are understood, the effect of many plant lipids remains to be determined. Acclimation of plants to non-freezing cold before exposure to freezing temperatures improves the outcome of plants, compared to plants exposed to freezing without acclimation. Arabidopsis thaliana plants were subjected to one of three treatments: (1) “control”, i.e., growth at 21 °C, (2) “non-acclimated”, i.e., 3 days at 21 °C, 2 h at −8 °C, and 24 h recovery at 21 °C, and (3) “acclimated”, i.e., 3 days at 4 °C, 2 h at −8 °C, and 24 h recovery at 21 °C. Plants were harvested at seven time points during the treatments, and lipid levels were measured by direct-infusion electrospray ionization tandem mass spectrometry. Ion leakage was measured at the same time points. To examine the function of lipid species in relation to freezing tolerance, the lipid levels in plants immediately following the freezing treatment were correlated with the outcome, i.e., ion leakage 24-h post-freezing. Based on the correlations, hypotheses about the functions of specific lipids were generated. Additionally, analysis of the lipid levels in plants with mutations in genes encoding patatin-like phospholipases, lipoxygenases, and 12-oxophytodienoic acid reductase 3 (opr3), under the same treatments as the wild-type plants, identified only the opr3-2 mutant as having major lipid compositional differences compared to wild-type plants.
Keywords: Arabidopsis thaliana; Freezing tolerance; Lipids; Lipidomics; Mass spectrometry-based lipid analysis